Cystic thymic degeneration with pseudoepitheliomatous hyperplasia in a Beagle puppy: an idiopathic lesion?. (May 2020) - Moretti, Giulia; Sforna, Monica; Caivano, Domenico; Mechelli, Luca; Bufalari, Antonello; Porcellato, Ilaria
A 6-mo-old female Beagle dog was inappetent and depressed. The radiographic, ultrasonographic, and computed tomographic examination of the chest revealed a 10 × 7 cm multicystic mediastinal structure interpreted as altered thymus, in association with moderate pleural effusion that laboratory tests confirmed as hemothorax. No history of trauma or anticoagulant drug intoxication was reported, and no coagulation disorders were detected. Afterward, medial cranial sternotomy was performed to remove the altered tissue. Histologically, this tissue was compatible with a thymic remnant, characterized by numerous cystic lesions, mostly blood filled and lined by flattened-to-cuboidal epithelial cells, occasionally projecting into the surrounding stroma, and forming cytokeratin-positive ribbons, trabeculae, and papillae. Lymphocytes were scant, and numerous areas of congestion and hemorrhage were present throughout the samples. This case of idiopathic thymic hemorrhage with cystic degeneration of the thymus and pseudoepitheliomatous hyperplasia was an incidental finding; the dog recovered from surgery uneventfully.